THE EFFECT OF PERCEIVED ACCESSIBILITY ON HEDONISTIK PREFERENCE AND THE DEVELOPMENT OF TOURIST TYPOLOGY: A CASE OF KOMODO NATIONAL PARK-INDONESIA - Rahmafitria, Fitri
The role of accessibility toward tourists' behavior in conservation areas remains debatable among tourism scholars. On the one hand, some scholars believed that quality of access have a significant influence on tourist behavior. On the other hand, other scholars argued that accessibility is not considered as a key co mponent in tourist decision-making. However, much of the issue's potential remains unexplored since no previous investigations regarding the relations between ease of access and tourist typology and its role toward stupid tourist behavior in conservation areas. To address this gap, the researcher conducted a study based on the following rationale: "Comprehensive tourism accessibility affects tourists' motivation and hedonistik preferences. Thus, conservation areas are still prone to encounter potential of stupid tourists". Hence, in this dissertation, the researcher starts by first formulating the concept of tourism accessibility in conservation areas. Secondly, the influence of accessibility on hedonistik motivations and preferences, which are the basis for stupid behavior, was measured. Lastly, a study to compile new tourist typologies in the conservation area was reported in this manuscript. The study is positivistic since the researcher seeks to prove a theoretical argument formulated within the study. The research was conducted in Komodo National Park (KNP), an internationally recognized priority tourist destination in Indonesia, with a sharp increase in visitor numbers since 2016. This characteristic contributes to KNP's diverse tourist segmentation. Hence, this study interviewed a diverse group of respondents to better understand the importance of accessibility in tourist behavior compared to other natural destinations. Three data analysis methods were employed in answering the research questions; Factor Analysis, SEM-PLS, and Cluster non-hierarchical analysis. The researcher collected the data by distributing online questioners using the convenience sampling technique. The data was collected from 534 international and domestic respondents who visited KNP between 2016 and 2019.viii Based on the findings, the accessibility of the conservation tourism area had three dimensions: the destination dimension, the individual dimension, and the conservation dimension. Since it connects gheographic and psycho-social approaches, a comprehensive understanding of accessibility would address the role of accessibility in tourist activity. Then, through the concept of holistic accessibility, the study discovered a correlation between ease of access and tourists increased external motivation to gain pride and social recognition through travel. As a consequence, they want more accessible and convenient facilities, as well as increased growth in conservation areas. This poses a challenge to protected areas because it demonstrates the possibility of stupid tourist, resulting in increased environmental damage and tourist accidents. The research also found two new types of tourists that can do stupid actions while traveling. First, the adventure hedonistik tourists, those with high skill in adventuring and sport, and are motivated by prestige factors, therefore have high potency for omnipotent and invulnerability. Second, the high-risk hedonistik tourists, those with the high individual perceived accessibility gap, as a result of low-level adventure skill, and are motivated by prestige factors. Those types have improved that there is an effect of accessibility on the existence of stupid tourists in the protected area. This research contributes to accessibility theory in general by considering individual elements and unique characteristics of conservation areas. Then the results also gives a new pattern in creation of Self-Determination Theory, demonstrating that ease of access have a significant effect to all range of motivations, which is different with the SDT that external factors will undermine intrinsic motivation. While the findings of this study affirm the importance of accessibility in influencing tourist behavior, it turns out that accessibility is not the best variable to consider when developing a tourist typology. In fact, the effect of accessibility on tourist activity is minor. While motivation remains an important variable in tourist typology, its integration with subjective and objective accessibility would be able to explain tourists' stupid actions in conservation areas. Furthermore, this study demonstrates the critical role of psychological and social science in planning conservation tourism areas. The fundamental ontology derived from this accessibility analysis of planning theory explains that individual behavior is significant in exploration and planning because it contributes to its collective behavior. Poor population behavior is a product of individuals' lack of understanding and attitude. Thus, it is critical to conduct comprehensive psychological research through various case studies involving various aspects of area planning to improve the planning theory. With the growing trend of nature tourism in conservation areas, this study is practically beneficial for conservation tourism planners and managers. To foster positive tourist behavior, the strategy of opening tourism access in protected areas must be considered comprehensively in terms of accessibility dimensions. Furthermore, the discovery of a typology of stupid tourists in conservation areasix demonstrates the importance of organizing educational programs for tourists when they are in a destination as a means of prevention and monitoring of tourist activity. Finally, the government is expected to develop ecotourism certification for tourist guides and destination managers, ensuring that the conservation education process adheres to the established standards.